Childrens Use and Understanding of Modal Expressions - MacDonald, Carol Ann (The University of Edinburgh, 1983)
The purpose of the study was to examine children's use and under¬ standing of modal expressions during middle childhood. The assumptions on which the work was based are as follows. First that any analysis of the developing modal system must be based on an adequate conception of the developmental endpoint viz. an adequate theoretical account of the adult English modal system. Secondly it is of value in studying children's language development to study both their spontaneous usage as well as their understanding of the same domain. Data derived from both sources can be integrated into a broad conception of this aspect of children's linguistic competence. The relevant philosophical, psychological, linguistic and develop¬ mental psycholinguistic literature on the area of modality is briefly reviewed. This allows us to establish central issues and to assess which questions seem appropriate to research. A working model of English modality is presented, which is based on the work of F.R. Palmer (1979), but contains the insights of other researchers such as Leech (1969), Perkins (1980) and Haegeman (1980). It is intended to give us an instrument by which we may usefully analyse our spontaneous and experimental data. Three types of modality - epistemic, discourseoriented (deontic) and dynamic - are established. As well as 'possibility' and 'necessity', 'futurity' (prediction) is presented as a third degree of modality. Auxiliary and non-auxiliary expressions of each type and degree are presented. Four observational case-studies (2 five year olds and 2 seven year olds) are described: the data are approached both qualitatively and quantitatively. No developmental effect is identified. There follows an analysis of five experimental tasks, carried out with 5, 6, 7, 9 and 11 year olds. The first study involved children transforming simple active declarative sentences into interrogatives, negated, and tense sequence forms respectively. In the second task children were asked to judge and correct deviant sentences, in which there was a redundant modal or quasi-modal verb. The third task required children to give acceptable paraphrases for modal verbs; in the fourth task children were to judge pairs of sentences containing different modal expressions as synonymous or nonsynonymous. The fifth task required children to make judgements about the strength of actuality implication and the deontic source of modals. It was found that, apart from the first, rather easier task, it was only at about the age of nine years that the children were proficient at these epilinguistic skills, and gave linguistic justi¬ fications for their judgements. Before this age children were likely to give pragmatic justifications. It is suggested that these skills may be related to the development of literacy. The case study children showed the predicted developmental effect in the performance on these tasks. It is suggested that research to establish the connexions between linguistic and conceptual modalities may now be pursued.